Psychological well-being during the Covid-19 pandemic among nursing students - Asri Wahyu Candrawati; Titin Sutini; Iwan Shalahuddin (Malahayati International Journal of Nursing and Health Science, 2021)
Background: The Covid-19 pandemic creates emergency situations that cause stressors to emerge. These stressors cause students to face challenges that can affect their life experiences and psychological well-being.Purpose: To describe the psychological well-being of nursing students during the COVID-19 pandemic.Method: A descriptive quantitative method with a sample of 290 nursing students from Padjadjaran University, selected with proportional stratified random sampling technique. The instrument used Ryff's Psychological Well-Being Scale with 42 questions and by an Indonesian version with a validity index 0.484-0.743 and alpha coefficient 0.304-0.580. This questionnaire used a Likert scale with a 1-6 range. Psychological well-being scores were grouped into 3 categories: high, medium, and low. Ethical clearance approved by committee ethics.Results: Finding that more than half of students (69%) had medium psychological well-being during the pandemic. The highest dimension score was on personal growth and positive relations, while the lowest was on autonomy and self-acceptance.Conclusion: The good condition of psychological well-being relates to the student's ability to fulfill the six dimensions during a pandemic. Educational institutions can work closely with the psychiatric nursing department to facilitate counseling programs during the COVID-19 pandemic.